2023
DOI: 10.3390/gels9030197
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimization of the Adsorption of Cr (VI) in a Chitosan-Resole Aerogel Using Response Surface Methodology

Abstract: In this paper, a model for Cr (VI) removal and optimization was made using a novel aerogel material, chitosan-resole CS/R aerogel, where a freeze-drying and final thermal treatment was employed to fabricate the aerogel. This processing ensures a network structure and stability for the CS, despite the non-uniform ice growth promoted by this process. Morphological analysis indicated a successful aerogel elaboration process., FTIR spectroscopy corroborated the aerogel precursor’s identity and ascertained chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…From Figure 4c,d, we concluded that increasing the volume of polysaccharide slightly decreased the diameter of the pores, as the precursor polysaccharide base presented a dense porous surface. The comparison of the open pores after the cross section in Figure 4c,d is recognizable in accordance with previous reports; when the amount of R limits the substrate for the structure of the three-dimensional network aerogel, although it strengthens the structure, the pores tend to increase in size [16,19]. From Figure 4d, it can also be seen that the aerogel had a flexible and porous structure with nonuniform axial growths, adjusted and controlled by the volume concentration and the crosslinking interaction between them, which determines the structure.…”
Section: Characterizationsupporting
confidence: 91%
See 2 more Smart Citations
“…From Figure 4c,d, we concluded that increasing the volume of polysaccharide slightly decreased the diameter of the pores, as the precursor polysaccharide base presented a dense porous surface. The comparison of the open pores after the cross section in Figure 4c,d is recognizable in accordance with previous reports; when the amount of R limits the substrate for the structure of the three-dimensional network aerogel, although it strengthens the structure, the pores tend to increase in size [16,19]. From Figure 4d, it can also be seen that the aerogel had a flexible and porous structure with nonuniform axial growths, adjusted and controlled by the volume concentration and the crosslinking interaction between them, which determines the structure.…”
Section: Characterizationsupporting
confidence: 91%
“…The resole (R) solution was made by dissolving phenol-formaldehyde resin (1:3.5) on NaOH at 0.1 M and stirring at 70 • C for 1 h. After that, the pH was adjusted, and the solution was placed in a rotary evaporator for 1.15 h in a water bath at 50 • C. The remaining liquid resole was removed and refrigerated. The synthesis of resole was detailed in our previous work [19].…”
Section: Preparation Of the Chitosan Pectin And Resole Solution For T...mentioning
confidence: 99%
See 1 more Smart Citation